Charge‐Rearrangement Averaged Dye Design for Precise, Real‐Time, and Portable Monitoring of Complex Solvent Environments - Li, Zhongyu; Sahoo, Smruti R.; Shen, Shen; Sun, Hao; Ågren, Hans; Zhang, Man; Baryshnikov, Gleb; Zhu, Liangliang (Angewandte Chemie International Edition, 2025)
Although solvatochromic materials provide visual function to differentiate solvents, they fail to precisely monitor complex solvent environments where solvent composition varies dynamically, because of an insensitive absorptional shift in these environments. Relatively, their fluorescence signal change, which should be more sensitive, has always been inefficient, resulting from inherent challenges in excited‐state dynamics. Here, we present a charge‐rearrangement averaged dye design, instead of traditional donor‐acceptor structures, to enable a high locally excited or twisted intramolecular charge transfer emission efficiency. A ratiometric dual‐fluorescence behavior can be observed along with a solvent‐dependent emission trade‐off rather than complete quenching. In this case, the dyes can not only precisely visualize various mixed solvents but also enable heterogeneous detection with over hundreds of reuse cycles after being integrated into a crosslinked polymer. The leading portable material achieves a self‐calibrated visual tracking of ethanol content (error<0.2%) with a robust working curve ( R 2  = 0.9992) while applied to E10 ethanol gasoline, operable via user‐friendly software analysis through mobile phone photography.